Menekan Turnover Intention dengan Meningkatkan Kepuasan Kerja dan Komitmen Organisasional - Sastrawan, I Putu Mangku Edy; Sugianingrat, I.A.P Widani; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Turnover is a problem faced by Auto 2000 where throughout 2019 there were a total of 12 employees who stopped working. Turnover intention is influenced by job satisfaction and organizational commitment. The purpose of this study was to determine the effect of job satisfaction on turnover intention directly and through mediation of organizational commitment. This research was conducted at Auto 2000 in Sanur Denpasar Branch on 45 employees using saturated sampling technique so that all members of the population were involved as respondents. Primary data collection using questionnaires and scales, measuring respondents' perceptions using a Likert Scale with five answer choices. The instrument was then tested with validity and reliability tests followed by path analysis techniques to answer the hypotheses that had been proposed. The results of data analysis prove that job satisfaction and organizational commitment have a negative and significant effect on turnover intention, job satisfaction has a positive and significant effect on organizational commitment, and organizational commitment mediates the effect of the job pontificate on turnover intention.